Memahami Perilaku Investasi Generasi Z: Peran Literasi Keuangan sebagai Pendorong Utama - Mu'afi, Muhammad Irfan (Universitas Halu Oleo, 2024)
This research aims to investigate the influence of financial literacy on investment interest in individuals. Investment interest is critical as it serves as the foundation for financial growth and future sustainability. The primary focus is on Generation Z, a group often perceived to lack sufficient financial awareness, prompting the need to understand how financial literacy can shape their preferences towards investments. This research method involves an online survey of a sample of Generation Z individuals who are still active students from the 2019-2022 cohorts and are typically aged between 18 and 22 years. Respondents are asked to fill out a questionnaire that includes questions about their level of financial literacy and their interest in engaging in investments. The data obtained is analyzed using statistical regression techniques to identify correlations between financial literacy and investment interest. In this study, the focus is to analyze the impact of financial literacy on investment interest among Generation Z students in the Yogyakarta region. Based on the research findings using Partial Least Square analysis, the conclusion drawn is that financial literacy has a positive and significant influence on investment interest.